"Diversión brillante y útil". Documentos para la historia del teatro en la Centroamérica del Siglo XIX - Molina Jiménez, Iván (1994)
Documents published in the Guatemalan and Nicaraguan pres son plays represented in that period, and which contribute to knowledge on the social history of theatre.